2014
DOI: 10.1097/qai.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

Needle Autopsy to Establish the Cause of Death in HIV-Infected Hospitalized Adults in Uganda

Abstract: Blind needle autopsy identified half of the major diagnosis. The addition of ultrasound guidance did not significantly improve the performance of needle autopsy. Needle autopsy is a valuable method to confirm causes of death in HIV-infected patients, especially for highly prevalent diseases like TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…Those who had MIA and those who did not were largely similar with regard to characteristics at enrolment and during follow up, although those with MIA were more likely to have been treated for TB between enrolment and death. This, together with the likelihood that MIA will miss some cases that may be identified by full autopsy [18], suggests that the prevalence of TB at death among the entire population of decedents in TB Fast Track may have been even higher than the almost 50% found in this sample. Nearly 90% of those with evidence of TB had disease in at least one extrapulmonary site and 38% were not on TB treatment at the time of death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those who had MIA and those who did not were largely similar with regard to characteristics at enrolment and during follow up, although those with MIA were more likely to have been treated for TB between enrolment and death. This, together with the likelihood that MIA will miss some cases that may be identified by full autopsy [18], suggests that the prevalence of TB at death among the entire population of decedents in TB Fast Track may have been even higher than the almost 50% found in this sample. Nearly 90% of those with evidence of TB had disease in at least one extrapulmonary site and 38% were not on TB treatment at the time of death.…”
Section: Discussionmentioning
confidence: 99%
“…Full pathological autopsy with visualisation and sampling of all organs remains the gold standard for assigning cause of death [17,18], but it is expensive, time consuming, and not well accepted by families, who are often required to provide consent [19]. There is growing evidence that minimally invasive autopsy (MIA) can provide useful information relevant to cause of death, particularly with regards to TB and other infectious diseases [20,21]; one study, involving 96 HIV-positive adults in Uganda, compared histology from MIA to that from full autopsy and found that MIA was 71% sensitive and 100% specific in detecting TB [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique enabled the diagnosis of 92% of cryptococcal brain infections in a post‐mortem study performed at Mulago hospital in Kampala, Uganda (Cox et al . ), and trained nurses could perform such a procedure in a village shortly after a child dies.…”
Section: What Type Of Research Needs To Be Undertaken?mentioning
confidence: 99%
“…This study was a substudy of an autopsy study that is described in detail elsewhere (20). In brief, we included HIV-infected adults (Ͼ18 years old) who died in one of the medicine wards of Mulago Hospital, Kampala, Uganda, during the period from February to June 2013.…”
Section: Methodsmentioning
confidence: 99%